2009
DOI: 10.1007/s11205-009-9452-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Income on General Life Satisfaction and Dissatisfaction

Abstract: Increasing evidence from the empirical economic and psychological literature suggests that positive and negative well-being are more than opposite ends of the same phenomenon. Two separate measures of the dependent variable may therefore be needed when analyzing the determinants of subjective well-being. We investigate asymmetries in the effect of income on subjective well-being with a single-item measure of general life satisfaction. Using data from the German Socio- Economic Keywords: generalized ordered pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 27 publications
4
74
0
2
Order By: Relevance
“…The different role played by comparison income and rank when accounting for high and low SWB levels is consistent with this view. Recently, Boes and Winkelmann (2009) have shown that the relationship between well-being and family income is not symmetric, with income being a more important source of negative well-being (when low) than of positive well-being (when high). According to the results, this also seems to be the case of unfavorable income comparisons and rank.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different role played by comparison income and rank when accounting for high and low SWB levels is consistent with this view. Recently, Boes and Winkelmann (2009) have shown that the relationship between well-being and family income is not symmetric, with income being a more important source of negative well-being (when low) than of positive well-being (when high). According to the results, this also seems to be the case of unfavorable income comparisons and rank.…”
Section: Resultsmentioning
confidence: 99%
“…Technically, this assumption stems from the fact that in models based on the cardinalization of the dependent variable as well as in standard ordered response models the gradient vector is the same for (1) is where the impact of comparison income on reported well-being, α c , is restricted to be constant across the SWB distribution. This is also the case of the Ordered Probit (OP) and, more generally, ordered response models, where the latent function has several threshold points that determine the observed value of SWB, Pioneered by Boes and Winkelmann (2009), the main advantage of the GOP is that it allows for a differential effect of the covariates in the different outcomes of the dependent variable.…”
Section: Introductionmentioning
confidence: 99%
“…The integral in equation (7) does not have a closed form solution; however, it can be numerically approximated by the GaussHermite quadrature method and the parameters can then be estimated by maximum likelihood (Boes and Winkelmann, 2010).…”
Section: Empirical Strategymentioning
confidence: 99%
“…However, none of the proposed explanations find empirical support. First, I controlled for socioeconomic status to account for variations in terms of life satisfaction across socioeconomic statuses (Boes and Winkelmann 2010) and to control for socioeconomic status effects on political participation (Verba et al 1995). However, the effect of life satisfaction on the protest activities of unemployed youth does not change when controlling for socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…However, a qualification has to be made regarding the latter argument, since life dissatisfaction has been found to have an effect only on the protest potential of specific groups, youth, working and middle class, but not for the general population. Indeed, working on the overall population, Flavin and Keane (2012) Firstly, life satisfaction can vary across socioeconomic groups; for instance those who face less financial difficulties may be less dissatisfied with their lives (Boes and Winkelmann 2010). Moreover, in examining the effects of unemployment on political participation, it is important to control for socioeconomic status.…”
Section: Hypothesesmentioning
confidence: 99%